Comparative molecular field analysis (CoMFA) and comparative molecular similarity index analysis (CoMSIA) study of mutagen X - Bang, SJ; Cho, SJ (WILEY-V C H VERLAG GMBH, 2004)
Mutagen X (MX) exists in our drinking water as the bi-products of chlorine disinfection. Being one of the most potent mutagen, it attracted much attention from many researchers. MX and its analogs are synthesized and modeled by quantitative structure activity relationship (QSAR) methods. As a result, factors affecting this class of compounds have been found to be steric and electrostatic effects. We tried to collect all the data available from the literature. With both CoMFA and CoMSIA various combinations of physiochemical parameters were systematically studied to produce reasonable 3-dimensional models. The best model for CoMFA gave q(2) = 0.90 and r(2) = 0.97, while for CoMSIA q(2) = 0.85 and r(2) = 0.94. So the models seem to be reasonable. Unlike previous result of CoMFA, in our case steric parameter alone gave the best statistics. Although the steric contribution was found to be the most important in both CoMFA and CoMSIA, steric parameter along with electrostatic parameter produced slightly better model in CoMSIA. Overall, steric contribution is clearly the most important single factor. However, when we compare chlorine and bromine substitution, chlorine substitution can be more mutagenic. This indicates that other factors such as electrostatic effect also influence the mutagenicity. From the contour maps, steric contribution seems to be focused on rather small area near C6 substituent of the furanone ring, rather than C3 substituent. Therefore the locality of steric contribution can play a significant role in mutagenicity.
Keywords: POTENT BACTERIAL MUTAGEN; TYPHIMURIUM TA100 MUTAGENICITY; CHLORINATED BUTENOIC ACIDS; DRINKING-WATER; 3-CHLORO-4-(DICHLOROMETHYL)-5-HYDROXY-2(5H)-FURANONE MX; MUCOCHLORIC ACID; HYDROXYL GROUP; STEPWISE REMOVAL; TREATED WATER; BY-PRODUCTS